Translating adult-oriented humour in children’s animated movies from English into Turkish: A corpus-based study - Semi, Gulce; Antonova-Unlu, Elena (Meta, 2024)
The aim of this study is to examine practices in translating adult-oriented linguistic humour in children’s animated movies. The research presents a corpus-based mixed study which draws insights from humour translation, translation of children’s literature (specifically the address problem) and audiovisual translation. The corpus-data were collected from forty randomly chosen Hollywood-made animated movies released between 2010-2019. In order to distinguish a humorous instance as adult-oriented, Akers’ (2013) adult humour categories were applied. The translation strategies applied to the target movies were categorised in accordance with their functions as retainment, replacement and omission. The classification of translation strategies used in this study was developed relying on the available translation strategies of Delabastita (1996) for puns, Leppihalme (1997) for allusions and Mateo (1995) for irony. Further, the data were interpreted both qualitatively, according to Asimakoulas’ (2004) theoretical model for the translation of humour, and quantitatively. The analysis revealed that to preserve adult-oriented humour, the most successful translation strategies belong to the Replacement Set while the least successful set is the Omission Set. According to the overall results, the general tendency is towards the elimination of adult-oriented humour.